Alternativas para a reprodução induzida, larvicultura e alevinagem do matrinxã, Brycon amazonicus (Spix e Agassiz, 1829) - Maciel, Rafael Lustosa (2020)
The matrinxã (Brycon amazonicus) is a native species of great importance for fishing and fish farming in the Amazon region. Because it is a species that has been cultivated for only a few decades, there is a lack of studies on the use of: synthetic hormones to induce the reproduction, larviculture and fingerling farming. Thus, the aim of this work was: to evaluate the use of alternative technologies for induced reproduction, incubation, larviculture and fingerling culture. The experiments were carried out at the Centro de Treinamento e Tecnologia de Produção de Alevinos de Humaitá, Amazonas, except for the larviculture that was carried out on a private property located in the rural area of the municipality. The first experiment evaluated females induced with the synthetic hormone Ovidrel® and its combination with carp pituitary gland in the main reproductive indices: oocyte weight, fertilization rate, hatching rate and post-larvae production; for males tested the viability of sperm production and the volume of semen produced. The females treated exclusively with the synthetic hormone did not spawn, it was only possible to perform the extrusion in the group that received the extract of the pituitary gland and in the group that received the mixture of synthetic hormone with the pituitary gland. However, for males the synthetic hormone made sperm production possible. The second experiment compared the incubation system with direct water flow with the recirculation system, with no significant differences in the evaluated indexes, however, the volume of water was significantly lower in the recirculation system when compared to the traditional system. In the third experiment, the viability of supplying brine shrimp to matrinxã larviculture was evaluated, comparing it with wild plankton from a previously fertilized nursery and with tambaqui larvae as forage. The group that showed the highest growth was the one that consumed plankton, however the highest survival rate was observed in the one that received the forage larvae. The fourth experiment evaluated the zootechnical performance of matrinxã fry fed with soybeans, soybeans fermented with probiotics and ration fermented with probiotics, with the ration being the control group. It was observed that the best zootechnical performance was obtained with the fermented ration, however, it did not differ statistically from the ration. It's possible conclude that the synthetic hormone can promote spawn in matrinxã when using as a preparatory dose and the pituitary gland as decisive for the induction of females, however the synthetic hormone shows better results for males. The incubation of eggs in a recirculation system does not affect the production of larvae, in addition to being more environmentally friendly since it uses a significantly smaller volume of water. The use of a mixture of brine shrimp and plankton may come to replace the use of foraging fish larvae. Regarding fingerling culture matrinxã, the best zootechnical results and the lowest cost of feeding were obtained when the animals were fed with fermented ration and ration.